2013
DOI: 10.1139/gen-2013-0210
|View full text |Cite
|
Sign up to set email alerts
|

TheDrosophila melanogasterseptin geneSep2has a redundant function with the retrogeneSep5in imaginal cell proliferation but is essential for oogenesis

Abstract: Septins are cytoskeletal proteins that form hetero-oligomeric complexes and function in many biological processes, including cytokinesis. Drosophila melanogaster has five septin genes. Sep5, which is the most recently evolved septin gene in Drosophila, is a retrogene copy of Sep2. Sep5 mutants appear wild type, whereas Sep2 mutant females are semisterile. Their ovaries have egg chambers containing abnormal numbers of nurse cells. The egg chamber phenotype is rescued to wild type by expressing a Sep2 cDNA, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…We previously found that Sep2 2 mutants, which contain a large deletion of the Sep2 coding region and are thus expected to be null mutants, have egg chambers with abnormal numbers of nurse cells ( O’Neill and Clark 2013 ). To determine if the Sep2 2 egg chamber defects are due to abnormal cystoblast divisions or fusion of multiple cysts into a single egg chamber, we counted oocytes and nurse cells per egg chamber by staining ovaries for Orb, which accumulates in the oocyte ( Lantz et al 1994 ), and DNA, which highlights polytene nurse cell nuclei ( Dej and Spradling 1999 ; Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously found that Sep2 2 mutants, which contain a large deletion of the Sep2 coding region and are thus expected to be null mutants, have egg chambers with abnormal numbers of nurse cells ( O’Neill and Clark 2013 ). To determine if the Sep2 2 egg chamber defects are due to abnormal cystoblast divisions or fusion of multiple cysts into a single egg chamber, we counted oocytes and nurse cells per egg chamber by staining ovaries for Orb, which accumulates in the oocyte ( Lantz et al 1994 ), and DNA, which highlights polytene nurse cell nuclei ( Dej and Spradling 1999 ; Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…w 1118 , y 1 w*; P{Sep2-GFP.SG}3 , w*; P{UASp-Sep1.GFP}3 , w*; P{UASp-Sep4.GFP}3 /TM3 Sb 1 , w*; P{UASp-Sep5.GFP}3 , w 1118 ; P{GAL4::VP16-nos.UTR}CG6325 MVD1 , y 1 w*; P{Act5C-GAL4}25FO1 /CyO , y 1 w*; P{tubP-GAL4}LL7 /TM3 Sb 1 Ser 1 , y 1 baz 4 /FM7a , pnut XP /T(2;3)SM6a-TM6B Tb 1 , P{hsFLP}22 , w* , w 1118 ; P{neoFRT}82B P{Ubi-GFP(S65T)nls}3R /TM6B Tb 1 , P{neoFRT}82B cu 1 sr 1 e s ca 1 , and y 1 w* P{PTT-GC}baz CC01941 were obtained from Bloomington Drosophila Stock Center at Indiana University. Sep2 2 , Sep5 2 , P{UASp-Sep2}18A , and P{UASp-Sep5}33B were generated as described in O’Neill and Clark (2013) . Flies were reared on standard cornmeal-molasses-agar media or Equation 4-24 plain instant media (Carolina Biological Supply Company, Burlington, NC) at 25° and 60% relative humidity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…albopictus is not surprising due to their well known cell division activities (Neufeld & Rubin, 1994), which could be involved in transiting from one developmental stage to the other, particularly in the production of new cells associated with their metamorphic processes. The increased expression in the adult could be linked to adult-stage related functions of septin genes, such as oogenesis and spermatogenesis (Hime et al, 1996;O'Neill & Clark, 2013). Since septins play important developmental and structural roles in eukaryotic organisms, and are associated with physiological and morphological abnormalities when altered, the identification and elucidation of their roles in individual species could provide valuable biological information for the development of less fit individuals to control mosquito population.…”
Section: Constitutive Expression Patternmentioning
confidence: 99%
“…As is known, genes are the basic molecular unit of heredity. However, the functions of genes have been widely reported to be redundant and reduplicative [ 1 , 2 ]. Some genes have turned out to be significant for survival, while others seem to be not necessary.…”
Section: Introductionmentioning
confidence: 99%